Factors Influencing Inappropriate Use of Antibiotics in Infants under 3 Years of Age in Primary Care: A Qualitative Study of the Paediatricians' Perceptions - José Arnau-Sánchez; Casimiro Jiménez-Guillén; Manuel Alcaraz-Quiñonero; Juan José Vigueras-Abellán; Beatriz Garnica-Martínez; Juan Francisco Soriano-Ibarra; Gema Martín-Ayala (MDPI AG, 2023)
Antibiotic consumption in infants of less than three years is higher than average the average consumption for general population. The aim of this study was to explore paediatricians' opinions regarding factors influencing inappropriate use of antibiotics in early infancy in primary care. A qualitative study based on the grounded theory using convenience sampling was conducted in Murcia Region, Spain. Three focal discussion groups were developed with 25 participants from 9 health areas (HA) of Murcia Region. Paediatricians perceived that health care pressure was an influential factor in the prescribing behaviour, forcing them to prescribe antibiotics for a rapid cure in unjustified circumstances. Participants believed that antibiotic consuming was related to parents' self-medication due to their perceptions about the curative potential of antibiotics together with facilities to obtain these agents from pharmacies without prescription. The misuse of antibiotics by paediatricians was associated to the lack of education on antibiotic prescription and the limited use of clinical guidelines. Not prescribing an antibiotic in the presence of a potentially severe disease generated more fear than an unnecessary prescription. The clinical interaction asymmetry was more evident, when paediatricians use trapping risk strategies as a mechanism to justify a restrictive prescribing behaviour. The rational model of clinical decision-making in antibiotic prescribing among paediatricians was determined by factors associated with health care management, social awareness and knowledge of the population and pressure of families' demands. The present findings have contributed to the design and implementation of health interventions in the community for improving awareness of the appropriate use of antibiotics, as well as for a better quality of prescription by peadiatricians.